MATERI PEMBELAJARAN BAHASA INDONESIA SMP DI KABUPATEN DEMAK PADA 2014 - nfn Sutarsih (Madah: Jurnal Bahasa dan Sastra, 2016)
Research Indonesian junior learning conditions in Kabupaten Demak is research to describe the state of Indonesian junior learning activities in Demak. The purpose of this study is to formulate the learning material presented by the Indonesian junior high teacher in Demak. The data in this study is the learning material presented Indonesian junior high teacher in Demak. In addition to the researchers themselves as instruments of data collection, the researcher equip themselves with instruments such as questionnaires and observation guidelines to capture the overall situation of the study. Analysis of the data used for the second stage of data capture. The eesults obtained are there some researchers Indonesian materials are easily taught to students because it is controlled by the teacher and there are some tough Indonesian material taught to students because it is less controlled by the teacher.